Dynamic Impacts of Lockdown on Domestic Violence: Evidence from Multiple Policy Shifts in Chile - Sonia R. Bhalotra; Emilia Brito; Damian Clarke; Pilar Larroulet; Francisco J. Pino (Institute of Labor Economics (IZA), 2021)
We leverage staggered implementation of lockdown across Chile's 346 municipalities, identifying dynamic impacts on domestic violence (DV). Using administrative data, we find lockdown imposition increases indicators of DV-related distress, while decreasing DV reports to the police. We identify male job loss as a mechanism driving distress, and female job loss as driving decreased reporting. Stimulus payments to poor households act on both margins, their impacts partially differentiated by lockdown status. Once lockdown is lifted, police reports surge but we see a ratchet effect in distress. Our findings accentuate the controversy around welfare impacts of lockdown mandates.
Keywords: J12; I38; H53; 330; public health; social safety net; domestic violence; COVID-19